2008
DOI: 10.1080/01902140802093212
|View full text |Cite
|
Sign up to set email alerts
|

Ischemic and Peroxynitrite Preconditioning Effects in Chronic Hypoxic Rat Lung

Abstract: Chronic hypoxic pulmonary hypertension is characterized by vasoconstriction and vascular remodeling and impaired endothelial nitric oxide (NO) production. Although ischemic preconditioning of the lung leads to protective effect against ischemic reperfusion injury, the mechanisms of this protection are not well documented in the lung. The aim of this study was to investigate the effects of chronic hypoxia on preconditioning induced by ischemia or peroxynitrite in isolated rat lungs. The isolated rat lung, from … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 41 publications
(65 reference statements)
0
4
0
Order By: Relevance
“…However, there are limited data on similar effects on the lung. In different animal models, it was found that IP, by blocking the pulmonary hilar blood flow, could attenuate the pulmonary dysfunction related to exposure to subsequent I/R [21].…”
Section: Discussionmentioning
confidence: 98%
“…However, there are limited data on similar effects on the lung. In different animal models, it was found that IP, by blocking the pulmonary hilar blood flow, could attenuate the pulmonary dysfunction related to exposure to subsequent I/R [21].…”
Section: Discussionmentioning
confidence: 98%
“…ONOO − is an oxidizing and nitrating molecule that has been implicated in cancer [13] and other acute [14] and chronic [15] diseases. ROS levels in tumor cells are controlled in a particular way, which stresses the importance of the development of novel ROS-targeted anticancer therapies.…”
Section: Ros Involvement In Cell Pathophysiologymentioning
confidence: 99%
“…Superoxide has been implicated in the pathology of many disease states, from cancer to cardiovascular disease, and is known to be able to damage DNA directly through oxidation, to inactivate cellular anti‐oxidants such as catalase and glutathione peroxidase and to activate proinflammatory nuclear factor‐ κ B . The reaction of superoxide with the NO radical is a critically important process that generates ONOO − , an oxidizing and nitrating agent that has been linked to the pathogenesis of cancer and other disease states . The ONOO − ‐induced oxidation of cysteine and nitration of tyrosine directly influences both the properties of proteins and cell signalling pathways, such as haemoglobin, inducible and endothelial NO synthases and Complexes I–IV of the electron transport chain.…”
Section: Reactive Oxygen Species Promote Cell Signalling and Angiogenmentioning
confidence: 99%